Penerapan Metode Rough Set Menganalisa Tingkat Kepuasan Mitra Cleaning Service - Dewi Berutu (ADA Journal of Information System Research, 2024)
PT. ISS Medan is a company operating in the service sector. The main activity of PT.iss Medan is to provide leading integrated facility services to more than 62,000 staff, 3,000 clients and nine branch offices in Medan. The company always tries to maintain a good reputation in the eyes of its customers. Good quality service will attract those who use the company's services. However The company does not have measuring instruments to determine the level of customer satisfaction with the services provided. Rough Set is a data mining method that is related to category analysis and data classification and aims to synthesize a conceptual approach from the data tables obtained. Rough sets find hidden relationships from data sets and reduct attributes from a series of attribute classifications, and the reduct will produce a general rule. The results of the customer satisfaction level rule illustrate that confidence is the main dimension in determining the level of customer satisfaction which is then supported by integrity. , pride (pride), and passion (desire).